Disruptions to smallholders' incomes and food security during a national lockdown: Evidence from two crop insurance trials in India - Ceballos, Francisco; Kannan, Samyuktha; Kramer, Berber (InsuResilience GlobalPartnership, 2020)
In early 2020, global alarms went off as a new virus threatened to take the lives of millions, prompting numerous countries into lockdown. Several months later, these and other restrictive measures remain, with economies worldwide finding themselves in dire straits. India, the 2nd most populous country and 6th largest economy in the world, and home to 126 million smallholder farmers, imposed one of the strictest lockdowns seen, with restrictions to the movement of people and goods at a time when farmers across several states were ready to harvest their crops.